Psychological Dynamics of Disaster Volunteers: Comperative Study Stress Coping Strategies From A Gender Perspective - Laili Alfita; Ampun Bantali; Ririn Rahmadhani (Manunggal Halim Jaya, 2026)
This study aimed to examine the dynamics of disaster volunteers by comparing stress-coping strategies from a gender perspective among volunteers at the Indonesian Red Cross (PMI) in Medan. The hypothesis proposed that male and female volunteers differed in their stress-coping strategies, with female volunteers assumed to demonstrate higher emotion-focused coping, whereas male volunteers were expected to use problem-focused coping more frequently. Stress coping was measured using a Likert-type scale. The study involved 56 participants, and the data were analyzed using an independent-samples t-test. The results showed an F value of 0.67 with p = 0.42 for problem-focused coping and an F value of 3.11 with p = 0.08 for emotion-focused coping. Because both significance values were greater than 0.05, the reported results did not indicate statistically significant gender differences in either problem-focused coping or emotion-focused coping. Therefore, based on the statistical values presented, the proposed hypothesis was not supported. Descriptively, female volunteers obtained a higher mean score for problem-focused coping (M = 34.767) than male volunteers (M = 33.500). Female volunteers also had a higher mean score for emotion-focused coping (M = 69.067) than male volunteers (M = 66.000). Although female volunteers demonstrated higher average scores for both coping strategies, these mean differences were not statistically significant based on the reported p-values.